In Vitro Disease Models for Understanding Psoriasis and Atopic Dermatitis - Sarama, Roudin; Matharu, Priya K.; Abduldaiem, Yousef; Corrêa, Mab P.; Gil, Cristiane D.; Greco, Karin V. (Frontiers in Bioengineering and Biotechnology, 2022)
Psoriasis (PS) and Atopic Dermatitis (AD) are two of the most prevalent and misunderstood inflammatory skin diseases. Dysregulations in the immune response are believed to play a crucial role in the pathogenesis of these conditions. Many other parallels can be drawn between the two conditions, as they are largely mediated through genetics, and characterised by dry, scaly skin caused by abnormal proliferation of epidermal keratinocytes. The use of in vitro disease models has become an increasingly popular method to study these conditions due to the high repeatability and accuracy of PS and AD conditions generated. However, due to the range of in vitro models available and the majority of these being in the early stages of production, areas of development are evident. Here we review the key features of PS and AD, the different varieties of models available, and discuss future research opportunities.